Digital flexion contracture caused by tophaceous gout in flexor tendon. (April 2019) - Tajika, Tsuyoshi; Kuboi, Takuro; Mieda, Tokue; Oya, Noboru; Endo, Fumitaka; Nakazawa, Takuro; Chikuda, Hirotaka
Gouty tophus is an unusual cause of digital flexion contracture. Awareness of this pathophysiology will lead to more confidence in proper treatment and surgical management of this rare condition. This report describes a case of digital flexion contracture by tophaceous gout distinguished between trigger finger and locking of the metacarpophalangeal joint. We found the flexor tendon with a deposited chalky white substance suggestive of gouty tophus intraoperatively. We performed tenosynovectomy and removed the chalky white substance to the greatest degree possible. Histological findings confirmed the diagnosis of gout. Postoperatively, the patient recovered nearly to a full range of motion of the affected digits. When meeting with the patient who has had hyperuricemia and who is unable to extend the affected digits suddenly, one must keep in mind digital flexion contracture caused by tophaceous gout.